Diseño de un sistema financiero, administrativo, contable, aplicado al comité de empresa " 26 de abril: trabajadores de Tabacalera Andina S.A. (TANASA)" - Parra Almagro, Paulina Alexandra (2012)
Presents the design of a financial system that is aimed at establishing economic and financial projections, allowing them to know and plan your income and expenses to determine the true status of the organization, meet the expectations and needs of its members, for leaders they can make good decisions and thus achieve efficiency.